Risks and bank performance in Jordan - Al Tarawneh, Marwan Hasan (2016)
Issue that revolves around risks and bank performance has always been an essential and critical element for banking sector in Jordan. Indeed, this study examines the impact of risks on bank performance in Jordan. Data of this study were retrieved from the Data Stream and annual reports of listed banks in Amman Stock Exchange (ASE). The sample of study comprises of 15 banks in Jordan and the period of study is confined to 2010-2014 which involved 75 observations. The dependent variable of this study is bank performance which was measured by using ROA while risks’ hypotheses variables are operational risk, credit risk, and liquidity risk. The results show that operational risk and credit risk have a negative significant relationship with ROA while liquidity risk is found to have a positive insignificant relationship with ROA. Also, the study discovers that the relationship between firm size and ROA is negatively significant while the relationship between bank age and ROA is found to be positively significant. Finally, the result of the relationship between management change and ROA is positively insignificant. Hence, hypotheses of significant relationship between operational risk and credit risk with bank performance are supported while hypothesis of significant relationship between liquidity risk and bank performance is not. Moreover, the study provides suggestions and recommendations for future research work.